2021
DOI: 10.1161/hypertensionaha.120.15247
|View full text |Cite
|
Sign up to set email alerts
|

4-Methylumbelliferone Attenuates Macrophage Invasion and Myocardial Remodeling in Pressure-Overloaded Mouse Hearts

Abstract: Cardiac wall stress induces local and systemic inflammatory responses that are increasingly recognized as key modulators of extracellular matrix remodeling. Hyaluronic acid interacts with immune cells and mesenchymal cells thereby modulating profibrotic signals. Here we tested the hypothesis that 4-methylumbelliferone (4-MU), an inhibitor of hyaluronic acid synthesis, would attenuate inflammation and extracellular matrix remodeling of pressure-overloaded myocardium in C57BL/6J male mice fed with 4-MU and subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Hackert et al . [ 26 ] found that expression of CCR-2, CCR-5, and C-X3-C motif chemokine receptor 1 (CX3CL1) increased in the heart, and monocytes were recruited into the heart tissue 3 days after TAC, while mRNA expression of chemotactic agents and adhesion molecules such as CX3CL1, CXCL1, and pro-inflammatory cytokine IL-1 was observed 7 weeks after TAC, indicating a shift towards the M1 phenotype in macrophages at this time point.…”
Section: Transverse Aortic Constriction Surgerymentioning
confidence: 99%
“…Hackert et al . [ 26 ] found that expression of CCR-2, CCR-5, and C-X3-C motif chemokine receptor 1 (CX3CL1) increased in the heart, and monocytes were recruited into the heart tissue 3 days after TAC, while mRNA expression of chemotactic agents and adhesion molecules such as CX3CL1, CXCL1, and pro-inflammatory cytokine IL-1 was observed 7 weeks after TAC, indicating a shift towards the M1 phenotype in macrophages at this time point.…”
Section: Transverse Aortic Constriction Surgerymentioning
confidence: 99%
“…In this issue of Hypertension , Hackert et al 1 make the initial observation that HAS2 (hyaluronan synthase 2) expression is increased in the heart in response to transverse aortic constriction, a well-established experimental model of cardiac fibrosis and heart failure (HF). To evaluate the role of hyaluronan synthesis in adverse cardiac remodeling, the authors use 4-methylumbelliferone (4-MU), a naturally occurring coumarin that inhibits hyaluronan deposition purportedly through depletion of Uridine di-phosphate glucose A, which is required for hyaluronan formation.…”
mentioning
confidence: 99%
“…Perhaps such a strategy could be pursued in addition to strategies, such as 4-MU. Either way, Hackert et al 1 remind us that there is a sweet smell of progress with 4-MU and biologically active sugars—we just need to make hyaluronan while the sun shines.…”
mentioning
confidence: 99%
See 1 more Smart Citation